Oględziny zwłok zakopanych i oględziny miejsca ujawnienia zwłok w przypadku podejrzenia przestępnego spowodowania śmierci — propozycja organizacji czynności procesowych. Studium przypadku - Wepsięć, Michał; Trzciński, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Inspections of corpses or human remains that have been buried should be carried out in close cooperation with police officers, a forensic doctor and archaeologists appointed as experts. Archaeological methods are able to accurately reconstruct the course of the burial itself and capture valuable evidence that can help in the reconstruction of the perpe-trator’s modus operandi and help to determine the identity of the victim.
Keywords: najlepsze praktyki; badanie zwłok; ekshumacja; archeologia sądowa